Does adult attachment mediate the relationship between primary emotion traits and eating disorder symptoms? - Roithmeier, Lisa; Fuchshuber, Jürgen; Prandstätter, Theresa; Andres, Deborah; Schmautz, Beate; Schwerdtfeger, Andreas; Unterrainer, Human-Friedrich (Frontiers in Psychology, 2024)
Objectives: Primary emotion traits and attachment patterns, have been linked to various mental disorders. This study aims to shed more light on the less studied relationship with eating disorder (ED) symptoms. Methods: A total of 921 non-clinical subjects (69.9% females) were assessed for primary emotions traits (BANPS-GL), attachment insecurity (ECR-RD8), eating disorder pathology (EDE-Q8). A theoretically derived model was evaluated by means of a path analysis with attachment anxiety as assumed mediator variable. Results: Global problematic eating behavior showed negative correlations with the positive emotions PLAY, CARE and LUST (r=-.10 to -.24), positive correlations with the negative primary emotions ANGER, FEAR and SADNESS (r=.12 to .27), as well as with attachment anxiety (r=.22, all p <.01). Path analyses revealed direct effects between eating behavior pathology with LUST (β=-.07 to -.15) and FEAR (β=.12 to .19; all p <.05). The association of SADNESS and Weight (β = .05) and Shape Concern (β=.06, p < .001) was fully mediated by attachment anxiety. Overall, the path model explained 17% of the variance for attachment anxiety and 6% of the Restraint, 13% for Eating, 10% for Weight and 14% for Shape Concern Subscales. Discussion: The findings shed light on the multifactorial relationship between affective traits, attachment security and eating disorder pathology. In line with previous research, the results emphasize the role of attachment and affective functioning in ED symptoms.